Pengaruh Konflik Pekerjaan-Keluarga, Kelelahan Emosional dan Stres Kerja terhadap Kinerja di PT Penerbit Erlangga Karawang - Khisomudin, Muhammad; Solehudin, Solehudin; Hasanah, Nunung Nur (Universitas Batanghari Jambi, 2024)
Dynamic company dynamics make human resources continue to innovate and be efficient in order to provide the best performance. The conflict between work demands and family responsibilities is increasingly gaining attention in the context of modern life. When work forces you to sacrifice time and attention that should be given to your family, conflict arises, causing a significant impact on an individual's emotional and physical well-being. Emotional exhaustion, which reflects a state of physical and mental exhaustion due to ongoing pressure, and job stress, which occurs due to a mismatch between job demands and the individual's ability to meet them, are the two main consequences of this conflict. This research method is quantitative using multiple linear regression analysis. The research results showed that work-family conflict, emotional exhaustion and work stress had an influence on performance.